HUBUNGAN KETERAMPILAN MEMBACA APRESIATIF CERPEN DENGAN KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS VII MTs. N LUBUK BUAYA PADANG - Naifah, Silmi; Basri, Irfani; Hayati, Yenni (Universitas Negeri Padang, 2016)
ABSTRACT The purpose of this jurnal is to describe the corelation between students’ reading appreciative short story and writing short story text skill of VII grade MTs. N Lubuk Buaya Padang. This research is quantitative research in term of description of corelation study. Based on the result of data analysis, it can be concluded that. First, students’ skill in reading appreciative short story of VII grade MTs. N Lubuk Buaya Padang is good with the avarage score 80,57. Second, students’ skill in writing short story text is good with the avarage score is 76,67. Third, based on t test, it can be concluded that there is significant corelation between students’ skill in reading appreciative short story and students’ skill in writing short story text of VII grade MTs. N Lubuk Buaya Padang because t counted is bigger than t table (12,19>2,021). Kata kunci: hubungan, membaca apresiatif, keterampilan menulis, teks cerpen